Analisis Motivasi Belajar Siswa Kelas II Sekolah Dasar Negeri - Utari, Dwi; Putra, Elpri Darta (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This study aims to describe the learning motivation of students in class II SDN 016 Kopah Village. This type of research is descriptive qualitative research. The subjects of this study were second grade teachers and all second grade students at SDN 016 Kopah Village. Data collection techniques used are interviews, observation and documentation. The data analysis technique used the Milles and Huberman model with stages, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the teacher always provides learning motivation to students during the learning process. given by the teacher, namely, 1) Praise Motivation, 2) rewards, 3) and the use of interesting activities during the learning process. Then, student motivation is divided into two, namely intrinsic motivation and extrinsic motivation. There are some students who are included in intrinsic motivation. Intrinsic motivation factors, namely, 1) the desire and desire to succeed, 2) the drive and need in learning, 3) the expectations and ideals, and 4) the appreciation in learning. The criteria for students who have extrinsic motivation are students who always need encouragement, praise and appreciation from the teacher. The conclusion of this study is, the learning motivation of second grade students of State Elementary Schools can be said to be good, seen from 13 students who have many intrinsic motivations in second grade students of SDN 016 Kopah Village.